The eﬀectiveness of m-holinolitics after transurethral resection of a benign prostate’s hyperplasia - P. V. Glybochko; K. L. Lokshin; Z. K. Gadzhieva; A. Z. Vinarov; M. R. Tangriberganov (Сеченовский вестник, 2011)
The aim of this research is to investigate the eﬀectiveness of m-holinolitics of those patients who have unsatisfactory results in transurethral resection of a TURP prostate. One of the most common diseases among older men, the benign prostate’s hyperplasia is a major medical and social problem nowadays.